The Dual Role of Public Debt in Morocco’s Investment Dynamics: Empirical Evidence - Zeroual Nouhaila; Doua Wissal; Aasri Mohammed Rachid; Khariss Mohammed (European Scientific Journal, ESJ, 2026)
This study examines the effect of public debt on investment performance in Morocco over the period 1990–2024. Gross fixed capital formation serves as the dependent variable, while public debt, government expenditure, inflation, and population growth are used as explanatory variables. Using the Autoregressive Distributed Lag (ARDL) approach, the analysis captures both short-run and long-run dynamics. The results reveal that in the long-run, public debt has a negative and statistically significant effect on investment, which suggests that excessive indebtedness challenges capital formation. In the short-run, only public debt has a temporary positive impact that fades over time. The negative and highly significant error correction term confirms a stable long-run relationship between the variables. Diagnostic tests indicate that the model is free from serial correlation, heteroskedasticity and instability. Globally, the findings underscore that while debt can initially stimulate investment, sustained debt accumulation could hinder it, highlighting the importance and need for prudent debt management and more efficient use of borrowed resources in Morocco. These outcomes suggest that an appropriate composition of public debt and efficient public investment management is crucial for sustaining private investment and long-term economic growth in Morocco, providing policy-relevant insights for fiscal authorities seeking to balance debt sustainability with investment-led development.